Card9 controls Dectin‐1‐induced T‐cell cytotoxicity and tumor growth in mice. Issue 5 (10th April 2017) - Haas, Tobias; Heidegger, Simon; Wintges, Alexander; Bscheider, Michael; Bek, Sarah; Fischer, Julius C.; Eisenkolb, Gabriel; Schmickl, Martina; Spoerl, Silvia; Peschel, Christian; Poeck, Hendrik; Ruland, Jürgen
Abstract : We identify Card9 as central regulator of Dectin‐1‐induced cross‐priming of cytotoxic T cells (CTLs) in mice. These Ag‐specific CTLs mediate potent antitumor immunity independent of inflammasome activity and NK cells. This pathway is a candidate for immunotherapy and vaccine development. Abstract : Activation of the C‐type lectin receptor Dectin‐1 by β‐glucans triggers multiple signals within DCs that result in activation of innate immunity. While these mechanisms can potently prime CD8 + cytotoxic T‐cell (CTL) responses without additional adjuvants, the Dectin‐1 effector pathways that control CTL induction remain unclear. Here we demonstrate that Dectin‐1‐induced CTL cross‐priming in mice does not require inflammasome activation but strictly depends on the adapter protein Card9 in vitro. In vivo, Dectin‐1‐mediated Card9 activation after vaccination drives both expansion and activation of Ag‐specific CTLs, resulting in long‐lasting CTL responses that are sufficient to protect mice from tumor challenge. This Dectin‐1‐induced antitumor immune response was independent of NK cell function and completely abrogated in Card9‐deficient mice. Thus, our results demonstrate that Dectin‐1‐triggered Card9 signaling but not inflammasome activation can potently cross‐prime Ag‐specific CTLs, suggesting that this pathway would be a candidate for immunotherapy and vaccine development.